DIGITALIZATION OF INDEPENDENT EDUCATION IN HIGHER EDUCATION - Rakhimov , Oktyabr Dustkabilovich (Innovative Development in Educational Activities, 2023)
The article contains information about the reforms implemented in the higher education system of Uzbekistan and the prospects of digitalization of higher education. The implementation of the credit-module system in the educational process of higher education and the role of independent education in it, the importance and necessity of using telecommunications educational materials based on digital technologies in the organization of independent education are based. The content of telecommunication educational projects and the methodology and stages of effective organization of telecommunication projects in the educational process of higher education are presented.